SISTEM INFORMASI EVALUASI KINERJA BIDANG KESEHATAN DI UPT PUSKESMAS ASEMBAGUS - Cindy Nur Dina Alifia; Zaehol Fatah; Neny Yuli Susanti (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2022)
Performance evaluation is an activity carried out to regulate health assessment standards in the Asembagus Situbondo sub-district for those who carry out examinations at the Asembagus Health Center. The data input process still uses the manual method, namely by recording using Microsoft Office Excel and carried out by one data analysis. In addition, data input takes a long time, because it consists of 7 health programs and 12 health sector indicators. With the performance evaluation information system, it is expected that data analyst officers can easily input data in a structured and efficient manner.